Study of the behavior of bridges under seismic loads considering soil-structure interaction - Baheddi, Mohamed; Youb, Youcef (Journal of Applied Engineering Science & Technology, 2015)
This work deals with the seismic stability of bridges considering the soil structure interaction, which is one of the most important phenomena in the field of earthquake engineering that can influence the behavior of the structure and thus its vulnerability. The main objective of this study is to see the influence of soil-structure interaction on the linear dynamic behavior of structures using two modeling approaches of the surrounding soil applied to the case of the viaduct 185.1 OA Bouira (Algeria). A second objective is to highlight the impact on the seismic response, when using different dynamic analysis methods, for the evaluation of the seismic behavior of concrete structures with boundary conditions applied as rigid or flexible to their foundations. The numerical simulation, carried out by using SAP2000 and based on dynamic computing finite element model, allowed to analyze soil-structure systems considering the effects of interaction by the response spectra method and the time history analysis. A parametric study was conducted to better understand the dynamic behavior of the bridge.
Keywords: Viaduct, Dynamic Analysis, Soil-Structure Interaction, Spring Model, Finite element Model